Controlling Bactrocera spp Fruit Flies Using Several Essential Oils from Clove, Lemongrass, Citronella Grass and Eucalyptus Plants on Chili Plants (Capsicum annuum L.) - Purnawan, Pupung; Hidayat, Yusup; Dono, Danar (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2025)
Fruit flies are the main pests on chili plants. Controlling fruit flies using synthetic insecticides can leave residues that are harmful to health. An alternative control that is relatively safe for the environment and human health is to use natural pesticides such as essential oils. This study aimed to obtain essential oils that are effective in controlling fruit fly attacks on chili plants. The study used an experimental method with a randomized block design (RAK) consisting of 5 essential oil treatments, namely clove leaf oil, lemongrass oil, citronella grass oil, eucalyptus oil and clove flower oil, along with a synthetic insecticide (Deltamethrin 25 g/L) and control. The experiment was repeated 4 times. Observations were made on the intensity of fruit fly attacks on chili fruit, insecticide efficacy, its effect on natural enemies and the weight of chili fruit. The results of the experiment showed that all essential oils tested, except clove flower oil, could significantly suppress Bactrocera spp. attacks on chili plants. The lowest percentage of fruit fly attacks was found in the clove leaf oil treatment, which was 59.17%, whereas in control it reached 93,84 %. The use of essential oils including clove leaf oil did not significantly affect the population of the natural enemies, ladybug (Harmonia. axyridis) and praying mantis (Mantis religiosa). All essential oils tested, except eucalyptus oil, also did not significantly affect the population of the natural enemy spider (Araneus ventricosus). There was no significant difference in the weight of chili fruit between all treatments tested.